The interior frontier: Exchange and interculturation in the Formative period (1000 B.C.-A.D. 400) of Quillagua, Antofagasta region, northern Chile. (20th November 2019) - Pestle, William J.; Torres-Rouff, Christina; Gallardo Ibanez, Francisco; Cabello, Gloria Andrea; Smith, Erin K.; Clarot, Alejandro
Abstract: While the village of Quillagua, a riparian oasis in the hyperarid Atacama Desert of northern Chile, is of limited modern importance, there is strong evidence to support the contention that during different prehistoric periods the village was a frontier between the populations of the Pampa, the Pacific Coast, the Loa River, and the Salar of Atacama. Indeed, it can be argued that it served as a node for systems of inter-regional exchange. Archaeological evidence indicates that this frontier function may have its origins as early as the Formative Period (1000 B.C.-A.D. 400), a crucial era of regional cultural change. Scholarship from across the social sciences suggests that frontier/border spaces can be dynamic zones of cultural innovation and that prolonged inter-group contact at such spaces can change perception and behavior, notions that we test through isotopic analysis and multi-source mixture modeling of individuals from two distinct precincts of Formative Period Quillagua. Ultimately, based on our paleodietary reconstructions, we find that some individuals from Quillagua were not simply engaged in systems of inter-regional economic exchange, but that their involvement likely fomented the creation of novel cultural forms.